Model Pendidikan Nonformal Melalui Eduwisata Rimba Adventure Untuk Peningkatan Literasi Sains Sejak Dini Di Sekolah Rimba - Nabila Pramidya Putri; Malpaleni Satriana; Husnawati Husnawati; Wahdatan Nisa (Jurnal Kajian Ilmiah, 2026)
This study aims to examine the non-formal education model through Eduwisata Rimba Adventure for Improving Science Literacy from an Early Age in Rimba Schools. The research approach uses qualitative data collection methods through observation, interviews, and documentation. Data analysis was carried out through data reduction, data presentation, and conclusion drawn, with validity tests using triangulation techniques and sources. The results of the study show that the nature-based edutourism model in construction through direct field interaction, environmental interaction, and experiential reflection supports the development of early childhood science literacy. This study shows that the nature tourism based learning model supports the development of early childhood science literacy through exploratory experiences and direct interaction with the environment.